2018
DOI: 10.17586/2220-8054-2018-9-1-17-20
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond aqueous dispersions as potential nanofluids: the determination of properties by thermal lensing and other techniques

Abstract: Thermal-lens spectrometry was used to characterize thermal diffusivity and thermal conductivity of aqueous nanodiamond dispersions at the level of mg/mL, accompanied by heat capacity, density, and viscosity measurements and modelling. The data from thermal lensing corresponding to thermal equilibrium show 3 -7 % increase in thermal conductivity of the studied dispersions, show good precision and agree with the existing data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In this case, a rough estimation for the RDDM gives the value no higher than 30 W m −1 K −1 . On the other hand, concentrated dispersions (50 mg mL −1 and above), for which the thermal conductivity is significantly different from the base fluid, as shown previously [ 25 ], have high viscosity values (from 1.5 times higher than that of water). It is noteworthy that the relative increase in dynamic viscosity compared to the base fluid can exceed the increase in thermal conductivity by no more than four times, in which case the addition of nanoparticles is practical [ 26 ].…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…In this case, a rough estimation for the RDDM gives the value no higher than 30 W m −1 K −1 . On the other hand, concentrated dispersions (50 mg mL −1 and above), for which the thermal conductivity is significantly different from the base fluid, as shown previously [ 25 ], have high viscosity values (from 1.5 times higher than that of water). It is noteworthy that the relative increase in dynamic viscosity compared to the base fluid can exceed the increase in thermal conductivity by no more than four times, in which case the addition of nanoparticles is practical [ 26 ].…”
Section: Resultsmentioning
confidence: 62%
“…However, it is problematic to compare thermal conductivity data to the starting nanodiamond materials as they are powders with different size distributions, porosity, and purity. Therefore, only for estimation, the paste-specimen cell was used for the RUDDM and RDDM powder measurements (we estimated the nanodiamond relative density—the ratio of the apparent density of the powder to the solid bulk [ 15 , 25 ]—as 15–17%, so the porosity was 83–85%). At 25 °C, the thermal conductivity was 0.26 ± 0.03 and 0.35 ± 0.04 W m −1 K −1 , respectively, which was consistent with the existing data [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the existing data has shown that, in many cases, the presence of carbon nanomaterials in large quantities (mg/mL level) increases the thermal conductivity of the dispersion [ 28 , 84 , 85 , 86 ]. As previously shown [ 27 , 78 , 87 , 88 , 89 , 90 ], an increase in the GO concentration leads to an increase in k of the dispersion, which is the main reason for the increase in thermal diffusivity.…”
Section: Discussionmentioning
confidence: 99%
“…The rarefied gas nanosuspension is a special case of a nanofluid. Nanofluids with spherical nanoparticles and carbon nanotubes have already been successfully used or are proposed for use in various applications (see for example [32][33][34][35]). The model of the viscosity of coarse dispersed fluid was developed by Einstein [36] and then generalized by many authors (see [37][38][39][40] and references therein).…”
Section: Modeling the Transport Processes In Rarefied Gas Nanosuspensionsmentioning
confidence: 99%